Influence of silicons of different structures on the hydration of compositional cements - Sokoltsov, Vladimir; Tokarchuk, Volodymyr; Sviderskyi, Valentin (Technology audit and production reserves, 2018)
The object of research is cement, which contains in its composition silica of various structures. The increase in the production of composite cements leads to the need to search for new active mineral additives. At the moment, the choice of mineral additives is made without taking into account the state in which the silicate component is located, therefore, it is necessary to develop certain criteria for the targeted selection of possible materials. This will reduce the cost of labor and financial resources to conduct relevant research. As it is known, silicates can be in a crystalline, amorphous and glassy state; therefore, the reactivity of various additives, even with the same chemical composition, can also differ significantly. It is proposed to study the effect of silica structure on hydration processes and properties of cements. The effect of silica in a different phase state (crystalline, amorphous, and glassy) on the hardening processes and physico-mechanical properties of composite cements has been investigated. It is established that the crystallinity degree of silica significantly affects the normal density of cement paste. Thus, the introduction of crystalline silica increases the normal thickness by 0.1–1.1 %, amorphous by 12.3–136.1 %, glassy by 11.2–56.2 %, compared with non-additive cement. The setting time of cement paste varies slightly. In the early stages of hardening, the rate of drop in strength is highest with the introduction of amorphous silica. For example, when enter 10 wt. % of crystalline silica shows a slight increase in the strength of the samples, compared with 8.2 % non-additive cement. The same amount of amorphous silica additive reduces strength by 33 %, glassy silica – by 19.2 %. This trend continues with increasing content of additives. The obtained research results allow to conclude that it is most appropriate to use in the production of composite cements mineral additives containing in their composition silica phases in a crystalline and glassy state.